TINDAK PIDANA PORNOGRAFI DARI PRESPEKTIF VIKTIMOLOGI - RAHMANIA, NUNUNG; NIRMALA, ATIKA ZAHRA; TAUFIK, ZAHRATUL'AIN (Universitas Mahasaraswati K. Mataram, 2024)
The development of technology and information has a positive influence on society, but on the other hand there is a negative influence in the form of the development of criminal acts of pornography which are increasingly spreading massively in society. The purpose of this study is to determine and analyze the form of victimization and victimogenic elements in the crime of pornography, the form of protection and the rights of victims in the crime of pornography, and the flow of victimology in accordance with the regulation of Law Number 44 of 2008 concerning Pornography. The research method used is normative juridical with statutory and conceptual approaches. The results of the research are: 1) The crime of pornography occurs either because of the victim himself (victimless crime) or other people and the form of victimization in the crime of pornography is making, using, spreading, broadcasting, exploiting, utilizing, downloading, letting, abusing power, listening, showing pornographic content either to yourself or to other parties. Meanwhile, the victimogenic factors of pornography crime are technological advancement, the function of supervision and control of the government that has not been optimal, and ethical and moral problems of society. 2) Forms of protection and rights of victims are in the form of guidance, assistance in the fields of law and health, and social recovery. 3) The appropriate victimology approach in pornography law is radical victimology and the protection of victims uses a service model